Can sustainable development save the rural coastal community? - Brown, Jennifer E., 1982- (2011)
The research is presented as the final component of a Master’s Degree in Natural Resource Management with a specialty in Coastal and Marine Management from the University of Akureyri in conjunction with the University of the Westfjords. It serves to answer if the theories of sustainable development can be used to assess the degree of sustainable development taking place in a rural coastal community in a meaningful way. Through the development of a Sustainable Development Assessment Tool for Rural Coastal Communities, sustainable development in Isafjordur, a community in the Westfjords of Iceland is assessed through a case study. The assessment tool is analysed using a SWOT analysis and is found to provide communities with a large amount of diverse information but the potential for bias exists. The research concludes that the strengthening of connections regionally and at the state-level would benefit the community of Isafjordur and communities like it in their pursuit of sustainable development. Recommendations include improvements of these connections through the diversification of the economy and the use of sustainable development principles to solve community issues.